Relationship Between Age, Gender, and Marital Status with The Intention to Disclose HIV Status Among PLHIV - Hutomo, Wahyuni Maria Prasetyo; Pramukti, Iqbal; Sari , Sheizi Prista (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Globally, Human Immunodeficiency Virus (HIV) remains a public health problem. The World Health Organization (WHO) reports 39.0 million (33.1-45.7 million) people living with HIV by the end of 2022, with two-thirds (25.6 million) in the African region. Based on national data in 2022, West Java has the 3rd highest number of HIV cases based on data and reporting from 2010-2022, which amounted to 52,970 cases, so it is necessary to disclose the status to the closest people to prevent transmission. HIV-positive status disclosure is the decision of PLWHA to disclose personal information about their disease and transmit it to others. This study aims to determine the relationship between age, gender, and marital status in disclosing HIV status in PLWHA. This study is a quantitative research, analytic research design with a cross-sectional design conducted on 74 PLWHA in Sumedang Regency Hospital. Data were analyzed using the chi-square test and Fisher's exact test. The results of bivariate analysis showed age Ϸ=0.033 and OR 2.739 (CI 95% 1.184-6.337), gender Ϸ=0.002 and OR 5.091 (CI 95% 1.712-15.139), single marital status Ϸ=0.004 and OR 4.4381 (CI 95% 1.628-12.099). (CI 95% 1.628-12.099) so that it is known that the variable most associated with disclosure of HIV-positive status in PLWHA at Sumedang District Hospital and the most associated with disclosure of HIV-positive status.